The Implementation of the SQ3R Strategy to Improve Reading Skill for Seventh Graders - Muhammad Wira Satriawan; Lilia Indriani; Dwitiya Ari Nugraheni (Didaktika: Jurnal Kependidikan, 2025)
This study aims to investigate the implementation of the SQ3R (Survey, Question, Read, Recite, and Review) strategy in improving the reading comprehension skills of seventh-grade students at SMP IT Ihsanul Fikri Kota Magelang. The research employed a classroom action research (CAR) design conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. Data were collected through reading comprehension tests, observation sheets, and student questionnaires. The results indicated a significant improvement in students' reading comprehension after the implementation of the SQ3R strategy. Students showed increased engagement, better understanding of texts, and improved ability to identify main ideas, details, and inferences. The findings suggest that the SQ3R strategy is an effective method to enhance reading comprehension among junior high school students.